Polyproline-rich peptides associated with Torpedo californica acetylcholinesterase tetramers - Toker, Lilly (Chem Biol Interact, 2020)
Acetylcholinesterase (AChE) terminates cholinergic neurotransmission by hydrolyzing acetylcholine. The collagen-tailed AChE tetramer is a product of 2 genes, ACHE and ColQ. The AChE tetramer consists of 4 identical AChE subunits and one polyproline-rich peptide, whose function is to hold the 4 AChE subunits together. Our goal was to determine the amino acid sequence of the polyproline-rich peptide(s) in Torpedo californica AChE (TcAChE) tetramers to aid in the analysis of images that will be acquired by cryo-EM. Collagen-tailed AChE was solubilized from Torpedo californica electric organ, converted to 300 kDa tetramers by digestion with trypsin, and purified by affinity chromatography. Polyproline-rich peptides were released by denaturing the TcAChE tetramers in a boiling water bath, and reducing disulfide bonds with dithiothreitol. Carbamidomethylated peptides were separated from TcAChE protein on a spin filter before they were analyzed by liquid chromatography tandem mass spectrometry on a high resolution Orbitrap Fusion Lumos mass spectrometer. Of the 64 identified collagen-tail (ColQ) peptides, 60 were from the polyproline-rich region near the N-terminus of ColQ. The most abundant proline-rich peptides were SVNKCCLLTPPPPPMFPPPFFTETNILQE, at 40% of total mass-spectral signal intensity, and SVNKCCLLTPPPPPMFPPPFFTETNILQEVDLNNLPLEIKPTEPSCK, at 27% of total intensity. The high abundance of these 2 peptides makes them candidates for the principal form of the polyproline-rich peptide in the trypsin-treated TcAChE tetramers.